Competitive aggressiveness and anger temporal trend approaching to water-polo match - Ferri, I. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Wide part of educational value of sport results from healthy, genuine and equilibrate emotional experiences. Emotions can widely influence sport performances: the IZOF model and the directional perception approach show the great subjectivity that characterizes emotions effects and explain how personal perception determines intensity and facilitative or dysfunctional direction of each emotions. Contact sport, more than others, can stimulate and carry aggressive and violent behaviors but very different levels of aggression acceptance exists (Kerr, 2002). The aim of this study was to examine temporal trend of competitive aggressiveness and anger in two different dimensions, intensity and direction, approaching to a match in a water-polo team. Methods: Participants were a sample of Italian young male athletes (N =15, mean age 15.9 years, SD ± 0.7) of a water-polo team, regularly involved in a national championship. They had on average 5.4 years of experience (SD± 1.3). Written informed consent was signed by all players parents. An adapted version of the CAAS (Competitive Aggressiveness and Anger Scale, Maxwell et al., 2007) was used to define a `state` assessment (48, 24, 2 hours before and 48 hours after the match). The score of each items ranges from 1 to 5 for intensity and from -4 to 4 for direction dimensions. Results: Aggressiveness and Anger mean scores were analyzed. Before the match aggressiveness intensity has been proved significantly lower rather than 48 hours after the match (p < .01) and results quite facilitative just before the match (t 4.2, p < .01). Anger intensity before the match can be overlapped to the levels reached after the game and after the match anger direction resulted significantly higher compared with the value obtained 48 hours before the match (t -9.2, p < .01). Discussion: Results confirmed that aggressiveness and anger temporal trend changes according to the IZOF model and the directional perception perspective. Further investigations are needed to better understand how manage aggressiveness and anger levels to improve athletes performances. Anticipating athletes intentions and perceptions could represent a great challenge to reduce violent behavior in sportive competitions (Russell, 1993).